Developing CAR-T/NK cells that target EphA2 for non-small cell lung cancer treatment - Kim, Seok Min; Lee, Soo Yun; Kim, Seo In; Bae, Ji Yeong; Hong, Jin Tae; Jo, Seona; Kim, Ji Hyun; Chung, Hyo-Young; Kim, Tae-Don (Frontiers in Immunology, 2025)
IntroductionChimeric antigen receptor (CAR) immunotherapy has revolutionized anticancer therapy, as it accurately targets cancer cells by recognizing specific antigens expressed in cancer cells. This innovative therapeutic strategy has attracted considerable attention. However, few therapeutics are available for treating non-small cell lung cancer (NSCLC), which accounts for most lung cancer cases and is one of the deadliest cancers with low survival rates.MethodsIn this study, we developed a new antibody targeting erythropoietin-producing hepatocellular carcinoma A2 (EphA2), which is highly expressed in NSCLC, and established CAR-T/ natural killer (NK) immune cells to verify its potential for immune cell therapy. The killing capacity, cytokine secretion and solid tumor growth inhibition of EphA2 CAR-T/NK cells were compared to normal T/NK cells.ResultsEphA2 CAR-T cells demonstrated superior killing capacity, enhanced cytokine secretion, and significant solid tumor growth inhibition. Additionally, they exhibited improved tumor infiltration in lung cancer models compared to normal T cells. The anticancer efficacy of the developed EphA2 CAR-NK cells was also confirmed, showcasing their potential as robust candidates for immune cell therapy.DiscussionThe findings of this study highlight the potential of CAR-T/NK cell therapy targeting EphA2 as an effective treatment for lung cancer, particularly NSCLC with high EphA2 expression. By leveraging the specific targeting capabilities of CAR-T cells and the unique properties of CAR-NK cells, this approach provides a promising therapeutic strategy to address the unmet needs in NSCLC treatment.